ДОСЛІДЖЕННЯ ДИНАМІЧНИХ ПРОЦЕСІВ У ВИСОКОЧАСТОТНИХ ПРИСТРОЯХ КОРЕКЦІЇ КОЕФІЦІЄНТА ПОТУЖНОСТІ - Рогаль, В.В.; Демченко, Ю.С. (Інститут електродинаміки НАН України, Київ, 2012)
The basic methods of correction of power-factor are considered. The models of corrector, which work according to the borderline control method, are built in the MATLAB environment (addition Simulink). Research of work of highfrequency devices of correction of power-factor is conducted. The diagrams of current of throttle and voltage on load of power factor corrector are indicated. The new model of corrector with an additional switching circuit of the transistor was created, which is more steady to reduction of resistance of load. The new algorithm of starting of corrector with precharged capacitor filter is offered. References 3, figure 1.